DEVELOPING COMMUNICATIVE SKILLS-BASED READING MATERIALS FOR TECHNICAL ENGLISH COURSE - Hasbullah M.Pd. (Cordova Journal : languages and culture studies, 2016)
Abstract: Reading is of para mount importance among other skills in English, particularly with in the English for Specific Purposes (ESP) instructional landscape. This study aims at developing appropriate communicative skills-based reading materialis for Technical English 1 (TE I) Course. The proposed materials had to go through expert verification and revisions. Then, they experienced field try-outs and revisions to be validated as afinal product. A recycle was done to streng then the validation. There are seven units of reading developed based on Contextual Teaching and Learning (CTL) method, completed with appropriate learning activities and assessment techniques. The implementation of CTL approach has brought about improvement in the teaching and learning process of TE 1 Course for CESP students.